Study on multi-scenarios regulating strategy of land use conflict in urban agglomerations under the perspective of “three-zone space”: a case study of Harbin-Changchun urban agglomerations, China - Zheng, Wei; Guo, Bin; Su, Hao; Liu, Zijun (Frontiers in Environmental Science, 2024)
Bin Guo executes the conception and framework of the article, formulating or evolving the overall research goals and objectives. He is also responsible for the overall coordination and scheduling of the project and the article, especially for critical reviews, comments, or revisions.Wei Zheng is primarily responsible for writing and adapting articles. He collects data and organizes and performs specific analysis of research questions and spatially presents and plots the results, and performs the corresponding authorial duties.Hao Su is responsible for the guidance and proofreading of research methods and models, as well as the review of data, etc.